Landscape architecture industrial training: Sustainable ability through the landscape industry demands / Ruwaidah Borhan and Atikah Fukaihah Amir - Borhan, Ruwaidah; Amir, Atikah Fukaihah (2021)
Industrial training is the platform for students in academic programs to get exposure to real-world experience and discover knowledge that is not taught in the syllabus. In the prospect of Landscape Architecture students, the students can utilize industrial training to gain valuable real-world experiences that will strengthen their positions, allowing them to gain an edge during job search (Neuman, 1999). This requires three-way communication among the educational institution, the student intern, and the industry worksite supervisor. Landscape architecture field is categorized as a professional area where the relationship between three parties are strongly needed. Thus, the aim of this paper is to identify the dimension of ability that is highly demanded by the industry from the industrial training students in a way to give contribution in organization of landscape architecture industry. Industrial training is often used as filtering devices by employers for the student’s ability to join the company in future. Qualitative data was conducted in this research to develop a model that consists of the dimension themes that are needed the most by the industry from the industrial training students. There are 6 significant themes developed in this research: (1) technical ability, (2) communications persuasive ability, (3) professionalism ethical values, (4) theoretical knowledgeable ability, (5) ideas and creativity, and (6) teamwork ability. The findings of the study may lead to improvements concerning the dimensions from the roots in diploma study that are needed to be considered in the future syllabus in order to develop and mold the ability required by industry.